A concise guide to communication in science and engineering - Foster, David H. (Oxford University Press, 2017)
"Success in scientific and engineering research depends on effective writing and presentation. The purpose of this guide is to help the reader achieve that goal. It enables students and researchers to write and present material to a professional modern standard, efficiently and painlessly, and with maximum impact. The approach is not prescriptive. Rather, the emphasis is on a logical approach to communication, informed by what needs to be achieved, what works in practice, and what interferes with success. Over 400 examples of good and bad writing and graphing are presented. Each is from a published research article and is accompanied by analysis, comment, and correction where needed. Journal reviewers' critiques of submitted manuscripts are included to illustrate common pitfalls. Above all, this is a "how-to" book, comprehensive but concise, suitable for continuous study or quick reference. Checklists at the end of each chapter enable the reader to test the readiness of a dissertation, journal submission, or conference presentation for assessment or review. Although oriented towards engineering and the physical and life sciences, it is also relevant to other areas, including behavioural and clinical sciences and medicine."-- Provided by publisher
Keywords: Technical writing.; elektronické knihy; electronic books